2020
DOI: 10.1177/0003702820961437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Beam Focusing Characteristics on Laser-Induced Breakdown Spectra

Abstract: The impact of altering laser focusing conditions on laser-induced breakdown spectroscopy experiments is investigated under ambient Earth laboratory and simulated Martian atmospheres. Experiments were performed in which the focal spot size was varied on a sample by altering the lens to sample distance with respect to targets of interest. Samples investigated include aluminum, copper, and steel. Specific neutral and ionic transitions of each sample were monitored. Atomic and ionic emissions show different intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Firstly, in the ablation process, whether it is plume or plasma still has not been studied, which is affected by many factors, such as laser parameters, focal conditions, and material properties. 26,27 When the uence of the ablation laser is below the ionization threshold, the ablated mass is only the vapor plume without free electrons. 24 If the energy of ablation laser is sufficient to overcome the threshold, plasma generated.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in the ablation process, whether it is plume or plasma still has not been studied, which is affected by many factors, such as laser parameters, focal conditions, and material properties. 26,27 When the uence of the ablation laser is below the ionization threshold, the ablated mass is only the vapor plume without free electrons. 24 If the energy of ablation laser is sufficient to overcome the threshold, plasma generated.…”
Section: Introductionmentioning
confidence: 99%
“…Qingdong et al found that the quantitative analysis accuracy of a fiberoptic LIBS system was slightly higher than that of a traditional LIBS system and a portable LIBS system [11,12]. Experimental parameters such as laser energy, delay time and resolution are also factors that researchers have often considered [13,[14][15][16]. Khater et al searched for stable conditions suitable for spectrochemical analysis by changing the laser energy [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Mars missions cited above calibrated their instruments using spectra collected at a uniform distance and a single plasma temperature (Anderson et al., 2022; Clegg et al., 2017). It is now apparent that plasma temperatures vary widely in Mars spectra collected under a range of target distances due to changes in the ablation spot size (Maurice et al., 2012, 2021; Melikechi et al., 2014; Mezzacappa et al., 2016; Surmick et al., 2021). Mismatches between lab data and spectra of unknowns measured on Mars may result in degradation of geochemical accuracy.…”
Section: Introductionmentioning
confidence: 99%